SPATIO-TEMPORAL ASSESSMENT OF VEGETATION REGENERATION IN AREAS AFFECTED BY PYROCLASTIC FLOWS AND SURGES A Case of Gunung Merapi National Park - , DEDY HUMAIDI, Dr. R. SUHARYADI, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Merapi Volcano eruptions have impact on the surroundings including Gunung Merapi National Park (GMNP). Pyroclastic flows and pyroclastic surges are able to cause serious damage to vegetation and causing land cover changes. Concerning the function of GMNP as conservation area, the information of what was the impact of volcanic eruptions to the vegetation and how the vegetation regeneration after the eruptions are important. The main aim of this research was to study the vegetation regeneration in GMNP areas after the 2006 and 2010 eruptions using remote sensing and GIS. This research used vegetation indices to detect changes in canopy cover which were then used as indicator of vegetation regeneration. The results showed that vegetation types affected in 2006 and 2010 eruption were mixed forest and shrub. GMNP zones affected in 2006 eruption were: sanctuary, mitigation, wilderness and traditional zones, while the 2010 eruption affected all zones: sanctuary, intensive use, mitigation, rehabilitation, religious and cultural, wilderness, and traditional. There were four vegetation indices tested (RVI, NDVI, SAVI, MSAVI2) for their correlations with canopy cover. Results from simple regression model concluded that NDVI with power regression model gave the highest R2 value. This model can explain 70% of variance in canopy cover. From the ANOVA analysis of vegetation regeneration after 2006 and 2010 eruptions, there were differences of vegetation regeneration within different landcover types and different GMNP zones. This study also found that the vegetation regeneration after 2006 eruption was influenced by four factors: distance to crater, aspect, elevation, and rainfall. While the vegetation regeneration after the 2010 eruption was influenced by two factors: rainfall and elevation.